Survei Persepsi Beban Perawatan Pengasuh Yang Berkaitan dengan Tindakan Terkait Ekskresi Pasien Penyakit Parkinson - Surya Syahputra Berampu (Lembaga Pengembangan Kinerja Dosen, 2022)
Parkinson's disease (PD) is a progressive disease in which competence in performing activities of daily living declines, increasing caregivers' perception of care burden. Care for excretion-related actions is frequently required in the context of motor and non-motor symptoms, and nursing content. Movement and dressing are examples of care. As a result, the care burden perception in relation to excretion-related actions was investigated and classified in this study based on severity and intra-day changes in symptoms. The study included 25 caregivers from the Gunma Prefecture Branch of the Japan Parkinson's Disease Association. The questionnaire items addressed perceptions of care burden in relation to nine excretion-related actions. The caregiver's movement was classified as easy (ON) or difficult (OFF) (OFF). The subjects were divided into three groups (1/2, 3, and 4) based on the severity scale developed by Hoehn and Yahr. The progression of symptoms was found to increase the perception of care burden. Furthermore, while the difference between ON and OFF was not statistically significant, care burden perception tended to be higher with OFF. The perception of care burden increased as PD symptoms progressed, indicating a proclivity toward greater effects of intra-day symptom variation This could be useful information to consider. Rehabilitation is linked to reducing caregivers' perceptions of care burden in the context of Parkinson's disease and/or reorganization/refurbishment of the domestic environment